2018
DOI: 10.1177/0018720818781192
|View full text |Cite
|
Sign up to set email alerts
|

Redundant Automation Monitoring: Four Eyes Don’t See More Than Two, if Everyone Turns a Blind Eye

Abstract: These findings may motivate safety experts to evaluate whether their implementation of human redundancy is vulnerable to social loafing effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…This dual-task design is also in line with other current studies focusing on human redundancy and social loafing effects in technical environments (e.g. Cymek, 2018). These studies use software simulations (microworlds) that are presented to participants on the computer (e.g.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This dual-task design is also in line with other current studies focusing on human redundancy and social loafing effects in technical environments (e.g. Cymek, 2018). These studies use software simulations (microworlds) that are presented to participants on the computer (e.g.…”
Section: Discussionsupporting
confidence: 66%
“…These studies use software simulations (microworlds) that are presented to participants on the computer (e.g. Cymek, 2018). In contrast to that, we had to create a physical task to introduce a physical robot as partner.…”
Section: Discussionmentioning
confidence: 99%
“…RQ 3: Are effort losses stronger in studies employing cognitive as compared with physical tasks? Pertinent research used both between-(e.g., Cymek, 2018;Ying et al, 2014) and within-subjects designs (e.g., Hüffmeier et al, 2017;Wittchen et al, 2007). On the one hand, within-subjects designs entail the risk that, in laboratory studies, people may change their behavior "due to cues about what constitutes appropriate behavior" (i.e., demand effects; Zizzo, 2010;p.…”
Section: Research Questionsmentioning
confidence: 99%
“…Fourth, studies were included if they provided an effect size or sufficient information to calculate an effect size. If an article provided insufficient data to calculate an effect size (e.g., Cymek, 2018), two attempts were made to contact the study author(s). In total, we contacted 29 authors by email, yielding 16 responses (55%).…”
Section: Criteria For Inclusion and Exclusionmentioning
confidence: 99%
“…The fault diagnosis and resolution process has been studied intensively in the nuclear power plant, air traffic control (Langer and Braithwaite, 2016;Trapsilawati et al, 2016;Borst et al, 2017), submarine (Roberts et al, 2017), and many other backgrounds (Vicente et al, 2004;Wickens et al, 2009;Sebok and Wickens, 2016). Operator performance of safety-critical and highly automated environments monitoring has also been studied (Funke et al, 2016;Cymek, 2018). Previous studies have shown that several key factors can influence operator performance during fault handling, including task complexity (Liu and Li, 2012), positional knowledge and skill (Littlepage et al, 2016), and environmental stress (Martin et al, 2019), etc.…”
Section: Introductionmentioning
confidence: 99%